(3OQGSI hJMdjd GdejRGfjI HGSJYeGd GdeDTQGJ hGdfSH GdeGdjIs (3eQab HJeGQjf eMdhdIs - (3HhjHGhf(B, (3eSYhOs ((3GdLRGFQ s (3OGQ EjdjGA ddfTQ hGdJhRjYs, 2024)
(3OQGSI h JMdjd GdejRGfjI eaghe GdejRGfjI h eVehfgG GdGfJbGd ef GdejRGfjI GdeMGSHjI Gdi GdejRGfjI GdeGdjI GjVG GdejRGfjI GdeGdjI h GdejRGfjI GdeGdjI GdeNJUQI , GdeDTQGJ GdeGdjI JMJhj Jbjje GdGOGA GdeGdj JMdjd GdejRGfjI HGSJNOGe GdeDTQGJ GdeGdjI , GdfSH GdeGdjI GdGWGQ GdfXQj ddfSH GdeGdjI h JMdjd GdejRGfjI HGSJNOGe GdfSH GdeGdjI (B.s
Keywords: (3GdejRGfjIs